Angiotensin-(1-7) Central Mechanisms After ICV Infusion in Hypertensive Transgenic (mRen2)27 Rats - Kangussu, Lucas M.; Melo-Braga, Marcella Nunes; de Souza Lima, Bruna Soares; Santos, Robson A. S.; de Andrade, Hélida Monteiro; Campagnole-Santos, Maria José (Frontiers in Neuroscience, 2021)
Previous data showed hypertensive rats subjected to chronic intracerebroventricular (ICV) infusion of angiotensin-(1-7) presented attenuation of arterial hypertension, improvement of baroreflex sensitivity, restoration of cardiac autonomic balance and a shift of cardiac renin-angiotensin system (RAS) balance toward Ang-(1-7)/Mas receptor. In the present study, we investigated putative central mechanisms related to the antihypertensive effect induced by ICV Ang-(1-7), including inflammatory mediators and the expression/activity of the RAS components in hypertensive rats. Furthermore, we performed a proteomic analysis to evaluate differentially regulated proteins in the hypothalamus of these animals. For this, Sprague Dawley (SD) and transgenic (mRen2)27 hypertensive rats (TG) were subjected to 14 days of ICV infusion with Ang-(1-7) (200 ng/h) or 0.9% sterile saline (0.5 μl/h) through osmotic mini-pumps. We observed that Ang-(1-7) treatment modulated inflammatory cytokines by decreasing TNF-α levels while increasing the anti-inflammatory IL-10. Moreover, we showed a reduction in ACE activity and gene expression of AT1 receptor and iNOS. Finally, our proteomic evaluation suggested an anti-inflammatory mechanism of Ang-(1-7) toward the ROS modulators Uchl1 and Prdx1.